Remoção de fármacos anti-hipertensivos em soluções aquosas utilizando carvão ativado produzido a partir do bagaço de malte - Dörtzbacher, Gabriel Facciochi (2020)
Persistent or emerging pollutants are compounds that, not eliminated by conventional treatments, started to be detected in low concentrations in the environment. Although they pose no immediate danger, their effects have recently begun to be felt. Among them are the pharmaceuticals, responsible for the therapeutic activity of the drugs. Pharmaceuticals are complex molecules developed with the objective of having the greatest possible stability, a characteristic that gives them the status of persistent. One of the most widely used classes of drugs are the antihypertensives. Adsorption is one of the most used methods to remove substances in low concentrations due to the simple operation and low cost. The most widely used adsorbent is activated carbon, which can be produced from biomass pyrolysis. Studies have concentrated efforts on the use of alternative materials as adsorbents. The objective of this work was the production of activated charcoal through the pyrolysis of beer residue (malt bagasse) and subsequent physical activation, in order to use it as an adsorbent in the removal of pharmaceuticals. The technique has the advantage of saving chemical solvents and generating by-products of economic interest: bio-oil and bio-gas. The activated carbon was characterized by the techniques of infrared spectroscopy, x-ray diffraction, nitrogen physisorption and iodine number. The yields of biochar, bio-oil and bio-gas were 24.2; 40.9 and 34.9%, respectively. The loss of mass in the activation step was 30.6%. The values were compared with similar studies and are related to the heating rate and pyrolysis temperature. The activated carbon was in amorphous phase, with the presence of oxygenated functional groups and a degree of aromaticity as a consequence of the activation step, resulting in a material with an acidic surface. Nitrogen physisorption identified a micro-mesoporous material, with a specific surface area of 242.2 m² g-1, an average pore radius of 13.1 Å, and an iodine number of 296.7 mg I2 g-1, similar to commercial samples. Charcoal was used as a one-component removal of amlodipine besylate and losartan potassium from aqueous solutions. In the dosage tests, the optimal proportion chosen for both drugs was 5 g L-1 , with removal above 99%. The pH study found that the adsorption benefited in the pH ranges from 4.0 to 9.0 for losartan and above 9.0 for amlodipine. The contact times to reach equilibrium were 24 and 48 hours for amlodipine and losartan, respectively. The differences in removal can best be explained by the difference in hydrophobicity of the drugs. The kinetic models that best represented the adsorption were Elovich (amlodipine) and pseudo-second order (losartan). The data were used to build the equilibrium isotherms, finding extremely favorable curves for both drugs. The most appropriate models to represent the adsorption balance of both drugs were those of BET and Redlich-Peterson. The maximum adsorption capacities in the Langmuir monolayer were 56.6 and 53.1 mg g-1 for amlodipine and losartan, respectively. Through Langmuir, it was identified that the affinity between adsorbate and adsorbent was greater for amlodipine.